2015
DOI: 10.1007/978-3-319-18365-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols in Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a common motor neurodegenerative disorder with multifactorial etiology that is an increasing burden on our aging society. PD is characterized by nigrostriatal degeneration which might involve oxidative stress, α-synuclein (αS) aggregation, dysregulation of redox metal homeostasis and neurotoxicity. Although the exact cause remains unknown, both genetic and environmental factors have been implicated. Among the various environmental factors tea consumption has attracted increasing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 187 publications
(171 reference statements)
1
41
0
Order By: Relevance
“…Other herbal plants, such as the leaves of green tea ( Camellia sinensis ), contain high levels of catechins and polyphenols (Peluso and Serafini, ; Stohs and Badmaev, ). Recent data on the neuroprotective and neuroregenerative effects of green tea containing polyphenols indicate that they do not just possess antioxidant and anti‐chelating properties but may directly interfere with aggregation of the α‐sinuclein protein and modulate intracellular signaling pathways, both in vitro and in animal models (Caruana and Vassallo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other herbal plants, such as the leaves of green tea ( Camellia sinensis ), contain high levels of catechins and polyphenols (Peluso and Serafini, ; Stohs and Badmaev, ). Recent data on the neuroprotective and neuroregenerative effects of green tea containing polyphenols indicate that they do not just possess antioxidant and anti‐chelating properties but may directly interfere with aggregation of the α‐sinuclein protein and modulate intracellular signaling pathways, both in vitro and in animal models (Caruana and Vassallo, ).…”
Section: Discussionmentioning
confidence: 99%
“…[37] A study reported that EGCG binds to α-synuclein by hydrophobic interactions in an unstable manner. It was implied that EGCG could potently remodel the aggregates of α-synuclein, thereby acting as a potential disease modifying agent for the treatment of Parkinson's disease and other α-synuclein-related disorders.…”
Section: As Cardioprotectivementioning
confidence: 99%
“…As mentioned above, Parkinsonʼs disease is characterized by the presence of Lewy bodies and Lewy neurites, which are protein aggregates composed predominantly of the presynaptic protein α-synuclein [36]. Although the role of α-synuclein in the pathogenesis of Parkinsonʼs disease is not completely understood, the stabilization of nontoxic aggregates could represent a potential therapeutic route [37], and the study on the anti-aggregative properties of natural products has been used as a strategy for the screening of potential protective agents against Parkinsonʼs disease [38].…”
Section: Other Experimental Models For Studying New Agents Against Pamentioning
confidence: 99%